PENGAWASAN DINAS LINGKUNGAN HIDUP TERHADAP IMPLEMENTASI UPAYA PENGELOLAAN LINGKUNGAN DAN UPAYA PEMANTAUAN LIGKUNGAN PADA PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA AIR PT. SUMATERA ENERGI LESTARI KABUPATEN PAKPAK BHARAT - Berutu, Muhammad Rizky; Muhibuddin, Muhibuddin; Abidin, Zainal (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2023)
Carrying out any development not only triggers economic growth, but also has an influence on natural resource utilization patterns and risks to the environment such as environmental damage and pollution. To maintain the stability of natural resource utilization patterns, supervision is necessary. The authority to supervise development that has an impact on the environment in Pakpak Bharat district is the Pakpak Bharat District Environmental Service. This research aims to analyze the supervision carried out by the Environmental Service regarding the implementation of environmental management and environmental monitoring efforts in the construction of hydroelectric power plants in the Pakpak Bharat Regency area, as well as the efforts made to address the legal implications arising from the construction of hydroelectric power plants by PT.- Sumatra Energi Lestari. The method used in this research is an empirical method with the nature of the research used being descriptive, the data sources used are primary data and secondary data. Based on the results of the study showed that the supervision of the Environmental Service was conducted based on Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management, namely direct and indirect supervision. Even so, but in the practice of supervision that has not been carried out as optimal as possible. In addition, the efforts of the Pakpak Bharat Regency Government in addressing the damage to the environment caused by the construction of PT. Sumatera Energy Lestari Power Plants issued a policy that refers to Article 76 of Law Number 32 Year 2009, namely the dismissal of temporary development. The author's suggestion is that the Environmental Service should improve its supervision further and provide training to improve the quality of supervision for environmental supervisors and take firm action against perpetrators of environmental damage or pollution, both in terms of administration and recovery fines.